Um estudo sobre as necessidades formativas dos professores de Filosofia na rede estadual de ensino médio da cidade de Santa Maria - Araújo, Márcia Eliana Migotto (2007)
This research was developed in the Course of Master's degree in Education, of Santa Maria's Federal University / UFSM, in Pesquisa Formation's Line, Know and Professional Development. Our objective was to verify which they are the teachers' of Philosophy of the state net of medium teaching of Santa Maria's city formative needs, starting from the analysis of the questionnaires sent to the teachers. The specific objectives were: 1 - to identify which the modalities of continuous formation are offered to the teachers of Philosophy of the state net of medium teaching of Santa Maria's city; 2 - to verify the teachers' of Philosophy of the state net of medium teaching of Santa Maria's city formative needs is assisting to the teachers' needs for the courses of continuous formation, offered by the schools of performance; 3 - to understand as the teachers of Philosophy is facing the changes of the medium teaching and of the discipline Philosophy in the state net of medium teaching of Santa Maria's city - 8th HAVE FAITH (Regional Coordenadoria of Education). The approach is qualitative and the used instruments werw a form and a questionnaire. To present research it presents a reading of the the teachers' of Philosophy formative needs in the state net of medium teaching of Santa Maria's city, starting from the teachers' description. Our reading, in certain sense, "the certain distance" was accomplished, because we just analyzed the teachers' considerations starting from the questionnaires for them answered. At the end, we approached some subjects of the teaching of the Philosophy and his/her reality in Santa Maria's city, starting from the descriptions done by the teachers in the questionnaire. We noticed that many are the presented subjects: in relation to the teaching of the Philosophy, a teaching prevails returned for the philosophical reflection. In relation to the conditions of the educational work, they come, in general, scarce resources, low wages, interdisciplinaridade lack, teachers and unfounded students. To conclude, we present some final considerações that we think to be opportune on the education of the Philosophy and the professors of the related one discipline.